Web-Based New Student Admissions Information System at the Adzkia Integrated Islamic Elementary School (SDIT) - Maikiansi, Maikiansi; Akbar, Aswin (Program Pascasarjana STIE Amkop Makassar, 2023)
The information system for admitting new students is one of the processes in educational institutions such as schools that are useful for making it easier to screen prospective students who will be selected according to the expected criteria and determined by the school. In this study the application was at the Adzkia Integrated Islamic Elementary School, which had been done manually and had not been computerized. The author is motivated to create an Information System for making a web about Admission of New Students at the Adzkia Integrated Islamic Elementary School. Admission of New Web-Based Students with the Prototype model development method and with an object-oriented system approach that is modeled using PHP, HTML and SQL which is able to manage data quickly and to avoid cheating entering data. Admission of New Students has several stages, namely registration, selection, and announcement of acceptance of new students.